Supervisory Controller Design for Reactive Power Compensation - Gelen, Ayetül; Gelen, Gökhan; Bıçak, Aykut (Osman SAĞDIÇ, 2020)
The process of reducing the phase difference between current and voltage as much as possible by balancing the reactive power is known as reactive power compensation. With reactive power compensation, over currents and voltage drops in the transmission lines are prevented and higher quality, cheaper, and more efficient energy is provided. Reactive power compensation is done by switching capacitors with proper values. In a reactive power compensation system, capacitors are switched on and off by a controller. The switching behavior of this system can be characterized as a discrete event system (DES) that has discrete states and the state evolution depends on the occurrence of asynchronous events. In this paper, the control mechanism of a reactive power compensation system is considered in the sense of DES. The system is modeled by using automata and supervisory control structures are computed. The supervisors are obtained by using the supervisory control theory (SCT). Supervisors in the form of monolithic, reduced, and modular are synthesized to correct the power factor. The computed supervisors are also integrated with the system and simulated. The total size of supervisors, ie the total number of transitions and states of each, are compared. The computed supervisors in the form of modular ones have the smallest size. According to simulation results, it is demonstrated that the power factor is successfully corrected by all of the computed supervisors. The presented study shows how to calculate controllers for reactive power compensation systems by using the supervisory control theory. Since the supervisory control theory used in the study is a formal controller computation method, the presented approach enables the computation of formal controllers for reactive power compensation systems. The use of formal methods in the synthesis of controllers offers significant benefits in terms of realization and verification.

Reaktif gücün dengelenerek, akım ile gerilim arasındaki faz farkının olabildiğince azaltılması işlemi reaktif güç kompanzasyonu olarak bilinmektedir. Reaktif güç kompanzasyonu ile iletim hatlarındaki aşırı akımlar ve gerilim düşümleri engellenerek daha kaliteli, daha ucuz ve daha verimli bir enerji sağlanır. Reaktif güç kompanzasyonu uygun değerdeki kondansatörlerin anahtarlanması ile yapılır. Reaktif güç kompanzasyonu sistemlerinde kondansatörler bir kontrolör tarafından devreye alınıp çıkarılmaktadır. Bu sistemin anahtarlamalı davranışı, durum değişimi asenkron olayların oluşumuna bağlı olan, ayrık durumlara sahip bir ayrık olay sistemi (AOS) ile karakterize edilebilir. Bu çalışmada, reaktif güç kompanzasyon sistemlerinin kontrol mekanizması ayrık olaylı sistemler açısından ele alınmıştır. Sistem, otomat kullanılarak modellenmiş ve bazı gözetici kontrolör yapıları hesaplanmıştır. Gözeticiler, gözetimli kontrol teorisi kullanılarak elde edilmiştir. Güç faktörünü düzeltmek için yekpare, indirgenmiş ve modüler biçimde olan gözeticiler hesaplanmıştır. Hesaplanan gözeticiler sistemle entegre edilerek simüle de edilmiştir. Gözeticilerin toplam büyüklükleri yani her birinin geçiş ve durum sayılarının toplamı karşılaştırılmıştır. Hesaplanan gözeticilerden modüler yapıda olanın boyutu en küçüktür. Simülasyon sonuçlarına göre, güç faktörünün hesaplanan tüm gözeticiler tarafından başarılı bir şekilde düzeltildiği gösterilmiştir. Gözetimli kontrol teorisi kullanılarak reaktif güç kompanzasyonu sistemleri için denetleyicilerin nasıl hesaplanabileceği sunulan çalışma ile gösterilmiştir. Çalışmada kullanılan gözetimli kontrol teorisi formal (biçimsel) bir kontrolör hesaplama yöntemi olduğundan, sunulan yaklaşım reaktif güç kompanzasyon sistemleri için biçimsel denetleyicilerin hesaplanabilmesini sağlamaktadır. Denetleyicilerin sentezinde biçimsel yöntemlerin kullanılması gerçekleştirme ve doğrulama açısından önemli faydalar sunmaktadır.
Reaktif Güç Kompanzasyonu için Gözetimli Kontrolör Tasarımı
Keywords: Engineering; Mühendislik